Advanced fuel formulations containing biodiesel : Real-world applications - Carlucci, Antonio Paolo; Jaliliantabar, Farzad; Hagos, Ftwi Yohaness; Rizalman, Mamat (Elsevier, 2023)
Increasing the investment required to extract oil resources, alongside the uneven distribution and fluctuating oil prices of these resources globally on the one hand and the environmental hazards caused by their extraction and consumption on the other hand, are the main challenges that have pushed governments to find appropriate fossil fuel alternatives, especially in the transportation sector. In light of the above, biodiesel production as a proper alternative to diesel fuel has been growing worldwide while compulsory mandates requiring mixing biodiesel with diesel, and financial incentives, have also been proposed and implemented. Although the physicochemical properties of biodiesel are generally close to diesel fuel, differences in oil feedstock properties and the production process procedures lead to variations in biodiesel properties and, consequently, diesel engine behavior when powered by biodiesel. Blending biodiesel with diesel fuel is a promising solution to overcome this challenge while benefiting the unique advantages of this renewable fuel. In addition, a dual-fuel mode of engine operation using biogas, natural gas, syngas, and alcohol could contribute to a more efficient combustion process minimizing the disadvantages associated with using biodiesel in engines. The present chapter critically reviews and discusses these solutions, shedding light on the existing gaps to direct future research.